'Two Young Ladies in Connection with a Certain School:' The Watson-Ketcheson Affair of 1952–53 and the Remains of Eugene R. Fairweather. Issue 1 (23rd March 2018) - Lofft, Jonathan S.
Abstract: Two young teachers posted at an Indian Residential School in Saskatchewan, Canada, sought to act as whistleblowers regarding abuse there in 1952–53. Theologian Eugene R. Fairweather of Trinity College, Toronto, acted as their advocate and spiritual advisor. A significant correspondence, mostly purged from the official record, considered the reports of the whistleblowers, their fate, and the fraught place of the Residential Schools in Canadian Anglicanism in the decades before the era of Truth and Reconciliation. This article examines the relevant correspondence, retained only in the archival remains of Fairweather at Trinity. The correspondence, which adds to existing narratives of Anglican complicity in and responses to abuse at the Schools, suggests that future research must scrutinize official as well as previously overlooked sources of information, particularly the archival repositories of universities and theological schools, in search of the truth.